Effectiveness of artificial intelligence in the treatment of dental caries: An integrative review (Research, Society and Development, 2021)
The artificial intelligence (AI) is a branch of computing science which uses similar algorithms as a specialist before making any decisions and solving complex issues. In health, the benefits occur from data generation to improve management processes, identifying better treatments and helping in prevention and disclosure early-stage diseases. The purpose of this survey was to perform an integrative review on modern literature about AI to early diagnosis caries injuries, considering the benefits, limitations and impact in society and oral health. An integrative review had been done by searching 6 English scientific articles using on-line databases: PubMed, Cochrane, Scopus and Web of Science, using keywords such as: dental caries, artificial intelligence and dentistry. Moreover, other 6 articles were found by manual research indexed from 2016 to 2020, which worked with case report titled in vitro and in vivo. After eligibility criteria, 12 articles fully published in English and Portuguese were analyzed. The studies have shown that several modern methods of artificial intelligence offered exactness, ease of diagnosis and treatment effectiveness. Nevertheless, this technique has been through an experimental phase, it is required enhancement to reduce mistakes and misconception caused by this system.